Local government response to urban biodiversity conservation challenges within a global biodiversity hotspot - McLean, Cameron T.; Roberts, Debra C.; Slotow, Rob (Frontiers in Sustainable Cities, 2025)
IntroductionThe post 2020 Global Biodiversity Framework advocates for a whole-of-government and whole-of-society approach to address the global biodiversity crisis, with increasing calls for local governments to play a more active role in biodiversity conservation. We present a local government led examination of tools aimed at increasing biodiversity protection, management, and ecosystem restoration in the City of Durban, located in a global biodiversity hotspot.MethodsUsing analytical frameworks and local government data, we assessed the efficacy of tools applied, and identified barriers and potential enablers to improve conservation outcomes.ResultsWe confirmed areas of success in the development of fit-for-purpose town planning tools that have contributed toward avoided loss of biodiversity, and the implementation of tools that have increased the protection of important biodiversity sites. Development of land management and restoration functions have further advanced conservation outcomes through restored ecological processes, and improved management of threats. Despite positive contributions to biodiversity conservation, several challenges persist, including unequal biodiversity protection and investment in relation to local population socio-economic status, cross-sectorial barriers, governance silos, and inadequate incentives for protection and management. Increasing biodiversity conservation on landholdings under traditional and private land tenure represents an important next step for the City. Upscaling of successful management tools, improving financial incentives for landowners, and adopting a more community centered approach to conservation governance, represent key opportunities for the City.DiscussionWe emphasize the important role that a local government can play in contributing toward broader biodiversity goals and identify opportunities and challenges in the development and application of biodiversity conservation tools at the local government scale, through the lenses of governance, equity and justice, and inclusivity.